Risk Management Using the HIRARC Method at the PT ASDP Pulau Baai Ferry Port, Bengkulu Province - Priyono, Broto; Diani, Oktrianti; Sucahyo, Eugeneus Gesang (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
The Baai Island Ferry Port serves a pioneer route from Baai Kahyuapu Island, a distance of 106 miles, with a travel time of approximately 13 hours using the KMP Pulo Tello. Observations indicate non-compliance with Standard Operating Procedures (SOPs) regarding the use of Personal Protective Equipment (PPE) during loading and unloading of goods and passengers, potentially leading to the risk of work accidents. This study used theHIRARCto identify, assess, and analyze work risks referring to the Regulation of the Minister of Manpower and Transmigration Number PER.08/MEN/VII/2010 concerning Personal Protective Equipment (PPE). The results of the study revealed various potential hazards, such as slipping, being hit by a vehicle, falling into the sea, transportation accidents, and exposure to hazardous materials (fuel and toxic vapors). The SOP is expected to be a guideline for all parties involved in port operations to minimize risks and improve work safety, especially in the loading and unloading of passengers and goods at KMP Pulo Tello.